Multi-crosslinked flexible nanocomposite hydrogel fibers with excellent strength and knittability. (3rd January 2023) - Pei, Minjie; Zhu, Di; Yang, Junfeng; Yang, Kaidan; Yang, Hongjun; Gu, Shaojin; Li, Weiqing; Xu, Weilin; Xiao, Pu; Zhou, Yingshan
Graphical abstract: Highlights: Multi-crosslinked Flexible CNC/PVAGMA/TA nanocomposite hydrogel fibers was prepared. The CNC/PVAGMA/TA nanocomposite hydrogels exhibited excellent tensile strengths as well as high-water content of 70 %. The hydrogel fibers can be easily knitted into various complex geometries or integral textiles. Abstract: Hydrogel fibers with excellent mechanical properties are requested for biomedical applications, especially for flexible and wearable devices. However, it remains a challenge to fabricate hydrogel fibers with both enough strength and high water content. Herein, we prepare cellulose nanocrystal/polyvinyl alcohol nanocomposite hydrogels by rapid covalent crosslinking and the subsequent strong hydrogen bonding interaction derived from tannic acid. The multi-crosslinked skeletal structure endows the hydrogels with excellent tensile strengths as well as high water content, compared to the polyvinyl alcohol-glycidylmethacrylate hydrogels. Notably, P10C5T15 hydrogel can lift loads to 4.375 kg, which is approximately 2353 times its weight. Subsequently, the flexible and mechanically stable hydrogel fibers are fabricated with a tensile strength of 7.3 MPa and a breaking elongation of 123.8 %. Furthermore, the fabricated hydrogel fibers can be easily knitted into various complex geometries or integral textiles, suggesting their great potential for woven smart devices.